2020
DOI: 10.1186/s12916-020-01734-3
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor binding protein-2: a new circulating indicator of pulmonary arterial hypertension severity and survival

Abstract: Background Pulmonary arterial hypertension (PAH) is a fatal disease that results from cardio-pulmonary dysfunction with the pathology largely unknown. Insulin-like growth factor binding protein 2 (IGFBP2) is an important member of the insulin-like growth factor family, with evidence suggesting elevation in PAH patients. We investigated the diagnostic and prognostic value of serum IGFBP2 in PAH to determine if it could discriminate PAH from healthy controls and if it was associated with disease severity and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…The excessive release of growth factors (IGF-BP2 in this case) during lung remodeling processes in the setting of post-capillary PH is also not surprising. Yang et al [32] found markedly increased plasma concentrations of IGF-BP2 in two independent pulmonary artery hypertension (PAH) collectives. In conclusion, the levels of su-PAR measured here could also be consistent with current literature.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive release of growth factors (IGF-BP2 in this case) during lung remodeling processes in the setting of post-capillary PH is also not surprising. Yang et al [32] found markedly increased plasma concentrations of IGF-BP2 in two independent pulmonary artery hypertension (PAH) collectives. In conclusion, the levels of su-PAR measured here could also be consistent with current literature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NT-proBNP in the urine of preterm infants has been shown to inform about pulmonary hypertension (Naeem et al 2020 ). IGFBP-2 is an indicator of pulmonary arterial hypertension (PAH) (Yang et al 2020 ) and can predict a decline of kidney function in type 2 diabetes (Narayanan et al 2012 ). FABP4 has been implicated in proteinuria and has been discussed as a marker of kidney glomerular damage (Okazaki 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, NT-proBNP in the urine of preterm infants has been shown to inform about pulmonary hypertension 40 . IGFBP-2 is an indicator of pulmonary arterial hypertension (PAH) 41 and can predict a decline of kidney function in type 2 diabetes 42 . FABP4 has been implicated in proteinuria and has been discussed as a marker of kidney glomerular damage 43 .…”
Section: Ards-specific Heterogeneity Of Molecular Associations Across...mentioning
confidence: 99%